2023
DOI: 10.1002/ejhf.2836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vericiguat on left ventricular structure and function in patients with heart failure with reduced ejection fraction: The VICTORIA echocardiographic substudy

Abstract: AimVericiguat significantly reduced the primary composite outcome of heart failure (HF) hospitalization or cardiovascular death in the VICTORIA trial. It is unknown if these outcome benefits are related to reverse left ventricular (LV) remodelling with vericiguat in patients with HF with reduced ejection fraction (HFrEF). The aim of this study was to compare the effects of vericiguat versus placebo on LV structure and function after 8 months of therapy in patients with HFrEF.Methods and resultsStandardized tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Whereas the baseline characteristics and main unadjusted primary outcomes according to prespecified index event subgroups have been reported, 3,4 we now provide new data informed by treatment assignment and the effect of multivariable-adjusted analyses of primary and secondary outcomes. We also assessed outcomes of patients randomized while in hospital, as well as immediately following hospitalization, to provide finer continuous detail on the association between time from index event and outcomes.…”
mentioning
confidence: 96%
“…Whereas the baseline characteristics and main unadjusted primary outcomes according to prespecified index event subgroups have been reported, 3,4 we now provide new data informed by treatment assignment and the effect of multivariable-adjusted analyses of primary and secondary outcomes. We also assessed outcomes of patients randomized while in hospital, as well as immediately following hospitalization, to provide finer continuous detail on the association between time from index event and outcomes.…”
mentioning
confidence: 96%
“…We appreciate the interest shown by Dr. Wang and colleagues regarding our recent publication. 1 They raise three issues germane to our results: we welcome the opportunity to respond.…”
Section: Reply To 'Vericiguat In Heart Failure With Reduced Ejection ...mentioning
confidence: 97%
“…We appreciate the valuable findings of Pieske et al 1 The authors should be congratulated for providing evidence of the effect of vericiguat on reversing cardiac remodelling, especially in the context of limited clinical understanding of vericiguat in HFrEF. However, we thought to discuss several important issues.…”
mentioning
confidence: 99%
“…We read with great interest the study by Pieske et al 1 on the effect of vericiguat, an oral soluble guanylate cyclase stimulator, on left ventricular (LV) structure and function represented by LV end-systolic volume index (LVESVI) and ejection fraction (LVEF) in patients with heart failure with reduced ejection fraction (HFrEF). In brief, this study was a pre-specified echocardiographic substudy of the VICTORIA trial 2 and demonstrated that significant improvements in LV structure and function occurred in both the vericiguat and placebo groups over 8 months.…”
mentioning
confidence: 99%